Strategy for enhancing the solar-driven water splitting performance of TiO2 nanorod arrays with thin Zn(O, S) passivated layer by atomic layer deposition. (20th November 2016) - Shin, Seung Wook; Suryawanshi, M.P.; Hong, Hee Kyeung; Yun, Gun; Lim, DongHa; Heo, Jaeyeong; Kang, Soon Hyung; Kim, Jin Hyeok
Graphical abstract: Highlights: The Zn(O, S)/TONR arrays were successfully designed and prepared using combination of hydrothermal and ALD route. 10 nm Zn(O, S)/TONRs shows significantly improved PEC performance as compared to that using 30 nm. The enhanced PEC by introducing Zn(O, S) layer may be ascribed to the light absorbing, passivation, and well-aligned band structure. Abstract: An array of one dimensional (1D) TiO2 nanorods (TONRs) has been regarded as an attractive candidate for electrochemical energy conversion and as storage device due to its large surface area, effiective light scattering, and undisturbed charge transport pathway. However, the high defect/trap densities on surface of the nanostructured morphology and architecture may generally hinder the performance enhancement by providing electron-hole recombination sites. Hence, the surface passivation of nanoarchitectures based photoelectrodes has recently received much attention as an effective strategy to enhance the charge-separation and charge-transfer processes in photoelectrochemical (PEC) water splitting devices. In particular, a coating layer with narrowing band gap materials can promote enhanced light harvesting in the UV–vis region as well as surface passivation, directly supplying a driving force for charge separation and charge transfer due to band alignment. In this paper, the surface of TONRs were passivated by 10 and 30 nm thick Zn(O, S) layers with a relatively narrow band gap using an atomic layer deposition technique to modulate the thickness exactly. The 10 nm Zn(O, S)/TONR array exhibits a significantly enhanced photocurrent density (Jsc ) of 5.94 mA/cm 2 at 1.23 eV vs NHE and an incident photon-to-electron conversion efficiency (IPCE) of 49% at 374 nm compared with that of TONR arrays (Jsc of 1.99 mA/cm 2 at 1.23 eV vs NHE and an IPCE of 20% at 380 nm). However, the PEC performance is worse in the 30 nm Zn(O, S)/TONR arrays, showing a Jsc of 3.09 mA/cm 2 at 1.23 eV vs NHE and an IPCE of 29% at 374 nm. To clearly demonstrate these PEC behaviors, the TONR and Zn(O, S)/TONR arrays were characterized by electrochemical impedance spectroscopy (EIS), open circuit voltage decay (OCV) measurement, and X-ray photoelectron spectroscopy (XPS). The above mentioned characterizations indicate that the enhanced PEC performance of the 10 nm Zn(O, S)/TONR array resulted from the (i) increased light harvesting in the UV–vis region, (ii) lower charge transfer resistance and (iii) high value of valence band offset (VBO, −1.44 eV) and conduction band offset (CBO, −1.2 eV) than those of the TONR. However, the deterioration of Jsc in the 30 nm Zn(O, S)/TONR array is attributed to the negative value of VBO (-0.13 eV) and positive value of CBO (+0.27 eV), as well as the higher charge transfer resistance to the electrolyte than that of the TONR arrays, despite of the improved light absorption in the visible region. The photocurrent densities of 10 nm Zn(O, S)/TONR and 30 nm Zn(O, S)/TONR photocathodes decay to 4.718 mA/cm 2 (5.90 mA/cm 2 at 0 min) and 2.212 mA/cm 2 (3.03 mA/cm 2 at 0 min) after 90 min, respectively, they retain of about ∼ 80% and 70% of its original values. These experimental results and discussions not only provide the physical insights into the surface passivation effect and band alignment but also can open a promising route to design the thin passivation layer having the narrowing band gap energy (1.0 eV ∼ 2.5 eV) on the 1D TiO2 nanostructure for further enhanced performance and realization of a TiO2 based PEC system.